Christianity in Egypt : A History of the Coptic Orthodox And Evangelical Presbyterian Churches - Parker, Michael, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2026., 2026)
Drawing on primary sources as well as imminent scholars in the field, Parker has written a history of Christianity in Egypt that is scholarly and accessible. It challenges the common assumption that Egyptian Christianity is backward and irrelevant. Rather, as Parker writes in the preface, "the history of Egyptian Christianity presented in the pages to follow is of a people who enjoyed a brilliant golden age, suffered a long era of heartbreaking debilitation, and have now entered a period potentially breathtaking revival." It is a story worthy in its own right but also inspiring and instructive for the global church.